SELF-EFFICACY BERHUBUNGAN DENGAN STRES MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI TAHUN 2021 - Mardiati Barus; Helinida Saragih; Jenita Kamsya Bakara (Jurnal Online Keperawatan Indonesia, 2022)
Thesis is the final stage of assessing student academics and has been set at the college. Students who are preparing a thesis will experience many difficulties, including determining the title of the thesis, difficulty obtaining references, supervisors who have a busy schedule, repeated revisions, etc. The problems experienced by students when working on their thesis turn into negative feelings that are prone to cause loss of motivation, lack of confidence and can trigger stress. Self-efficacy is an important thing that a student must have. Self-efficacy possessed by individuals can help individuals to be able to deal with various situations. This study aims to analyze the relationship between self-efficacy and stress of bachelor of nursing students who are working on their thesis in the final semester at STIKes Santa Elisabeth Medan 2021. The research method used is a correlation research design with a cross sectional approach. The populations in this study are 109 people, the number of respondents are 105 people. The sampling technique is the total sampling technique. The results show that 80 people (76.2%) have moderate self-efficacy and 54 people (51.4%) have mild stress levels. The results of the spearman rank statistical test show that the value of r = (-.316) and p (value) = 0.001 (p <0.05), so it is concluded that there is a significant relationship between self-efficacy and student stress. Suggestions in this study are that students are expected to increase self-efficacy so that they can complete the final project as much as possible.